VD_FINDINFO HC / 2012 / 557 vom 7. August 2012 - VD Tribunal cantonal (2012)
PROTECTION DE L'UNION CONJUGALE, TRANSACTION JUDICIAIRE, VICE DU CONSENTEMENT | 176 al. 1 ch. 1 CC, 176 al. 1 ch. 2 CC, 176 al. 3 CC, 23 CO, 24 CO, 241 CPC (CH), 276 al. 3 CPC (CH)